KERAGU-RAGUAN VAKSINASI COVID-19 BERHUBUNGAN DENGAN KECEMASAN KESEHATAN DI MASYARAKAT - Amita Audilla; Aesthetica Islamy (Jurnal Ilmu Keperawatan Komunitas, 2022)
Introduction: Covid-19 vaccine was very important to prevent the spread of Covid-19. Our government has made Covid-19 vaccination program, so it can be followed by community. However, there were still many people who have not vaccinated caused by many things that lead to public hesitant about participating government's vaccination program. This study aims to determine the relationship between hesitancy of vaccine Covid19 and health anxiety in community.. Methods: This study used a cross-sectional research design, and used questionnaire to collect data. Sampels are people in Boyolangu Village. Sampling method was consecutive sampling (N=122). Study was held on June 2021. Vaccination hesitancy was refer to delay in acceptance or refusal Anxienty scored was analyze byHamilton Rating Scale for Anxiety (HRS-A). Result: The results of this study indicate 75,5% vaccination program scope. From 122 samples, 98 (80,3%) respondents have Covid-19 Vaccine Hesitancy and 64 respondents (52.5%) experienced anxiety. Chi-square test showed significant relationship between heshlitancy of vaccine covid-19 and health anxiety p<0,05. Discussion: Hesitancy about participating Covid-19 vaccination were still quite high in community. So it was necessary for government and health workers to continue to promote education about importance of vaccine covid-19 by using a therapeutic communication approach and other method which can community accepted. Keywords: hesitancy, anxiety, vaccine Covid-19